Ballistic Impact Response of Woven Hybrid Coir/Kevlar Laminated Composites - A.R, Azrin Hani; N.S, Azman; R., Ahmad; M., Mariatti; M.N, Roslan; N., Marsi (EDP Sciences, 2016)
The effects of different laminated hybrid composites stacking configuration subjected to ballistic impact were investigated. The hybrid composites consist of woven coir (C) and woven Kevlar (K) layers laminated together. The samples of woven coir were prepared using handloom device. The composites were produced by stacking the laminated woven coir and Kevlar alternately with the presence of the binder. The samples were tested under ballistic impact with different stacking configuration. The results obtained had successfully achieved the National Institute of Justice (NIJ) standard level IIA with energy absorption of 435.6 kJ and 412.2 kJ under the projectile speed of between 330 m/s and 321 m/s respectively. Samples that having Kevlar layer at the front face and woven coir layer as back face achieved partial penetration during projectile impact. This orientation is proven to have good impact energy absorption and able to stop projectile at the second panel of the composites.